Is the racewalking biomechanics significantly influenced by coaching? - Jurlin, K.; Babic, V.; Dolenec, A. (Kinesiologia Slovenica, 2023)
While there is a significant number of analyses of influence of coaching and training content on performance, detailed analyses linking teaching the technique and biomechanics indicators in literature are rather scarce. The purpose of the study was to determine the differences between two groups of racewalkers in the selected variables describing their gaits. The research method consisted of measuring ground reaction forces as well as kinematics of motion recorded by video cameras and the OptoJumpNext system of 14 athletes from two distinct training groups of athletes walking at individually determined speed. To identify the differences in 9 key variables between the two groups, a two-sample unpaired T-test was performed, which was also controlled by Cohens\' effect size indicator. The main finding of the study is that 5 key variables unrelated to walking speed were statistically different between the two groups, with Group A (predominantly \"M\"-shaped) having a lower ratio of peak ground reaction force (GRF) to GRF at 70% of the contact phase (p=0.0000), lower ratio of total GRF at the end and beginning of the interval 70% - 80% (p=0.0006), greater pelvic rotation (p=0.0056) and a more upright posture with lower forward pelvic tilt (p=0.0001) and lower backward thoracic tilt (p=0.0000). There were no significant differences between the two groups in two variables describing upper body movement i.e. arm-swing angle and thoracic rotation. Another variable (peak GRF) was also statistically different between the two group (p=0.0000), but this variable is related to the walking speed, which was not identical for the two groups. In conclusion, differences in the selected biomechanical indicators, that are trainable according to literature, may have been influenced by apparently different training approaches applied within the two groups of athletes. We suggest that, although the gait in racewalking is rather strictly defined by the rules, the above variables can and should be controlled and influenced by training to develop a smooth racewalking technique with lower peak ground reaction forces.